80th birthday of professor Bronisław Jasicki - Sikora, Paweł (Anthropological Review, 1986)
Professor Bronisław JASICKI was born in Sporysz on the 12th of January 1907. Since 1928 he has worked at the Jagellonian University, at first under the direction of Professor J. Talko-Hryncewicz, then Professors Kazimierz and Eugenia Stołyhwo. He devoted his entire life to anthropology. He directed and participated in research projects in ontogenetics (including research on the population of the Żywiec region). He is an author of numerous and original works in this field. For many years he was the head of the Anthropology Division of the Jagellonian University. He educated many anthropologists as a promotor and reviewer of numerous master theses, doctoral dissertations and works qualifying for the position of an assistant professor and professor. He has made an invaluable contribution to the development of Polish anthropology.